PENINGKATAN HUBUNGAN MASYARAKAT MELALUI KEPEMIMPINAN KOMUNIKATIF DI SD IT AL-AMBARI BUMIAYU - Saebani, Muhammad (Penerbit CV Tentrem Karya Nusa, 2018)
This methodology uses descriptive qualitative which the method is purpose to describe the concept of the principle of SD IT Al-Ambari Bumiayu to increase the internal and external human relations through communicative leadership. The data of this research was took by using interview, observation and documentation. Then, the data was analyzed using reduction, presentation and a conclusion. The result of this research shows that the practice of the communicative leadership of SD IT Al-Ambari Bumiayu is the way to focus of the educatio servicing to fulfill the expectation, requirement and goal from the external society. The increasing of human relations will be conduct if the expectation, requirement and goal is achieve.Key Words: communicative leadership, increasing, human relations.